For 5G applications, high-gain patch antenna in Ka-Band - Safa Nassr Nafea; Nasser N. Khamiss (Institute of Advanced Engineering and Science, 2023)
The fifth generation (5G) of telecommunications is an attractive application for many researchers during the last years. The 5G requires high date rate with low latency communication medium and patch antenna was used recently for this application. In this article a patch antenna for 5G at 38 GHz was proposed. This article worked on enhancing the gain of patch antenna at Ka-Band and reducing side lobes level (SLL) in radiation pattern. The gain of the patch antenna was improved using a reflector layer located under antenna’s ground with free space air gap separating between two layers. Moreover, the SLL were reduced to satisfy low latency condition for 5G communications. The proposed antenna shows high gain around 8.10 dB with high front-to-back (F/B) ratio of 16.24 dB and wide operating bandwidth around 1.4 GHz for high data rate requirements as well as having reduced overall size antenna. The article based on analytical calculations for patch dimensions and optimization procedure to achieve the desired performance of antenna. Computer simulation technology (CST) had been used as an environment for simulation.